Degradation of polyimide under exposure to 90 keV electrons. Issue 7 (20th March 2017) - Plis, Elena; Engelhart, Daniel P.; Barton, David; Cooper, Russell; Ferguson, Dale; Hoffmann, Ryan
Abstract : Interaction of high energy electrons with spacecraft materials, such as polyimide (PI, Kapton ® ), is known to cause their physical degradation. In this paper, we investigated chemical and optical changes in Kapton ® during and after irradiation with high energy (90 keV) electrons. Several complimentary characterization techniques were utilized to qualify and quantify radiation induced property changes in the material, including directional‐hemispherical reflectance (DHR) coupled with Fourier transform infrared (FTIR) spectroscopy, electron paramagnetic resonance (EPR), and the surface potential decay method. It was found that the conductivity of radiation‐damaged PI is significantly increased compared to that of the pristine material. This change is attributed to the creation of radicals during irradiation, which could play a critical role in the transport of electrons through the bulk of the damaged material. Excessive radicals are likely originating from a radiation‐induced breakage of phenyl rings and/or ether bridges forming a metastable carbonyl.